Variations of Soil Microbial Community Structures Beneath Broadleaved Forest Trees in Temperate and Subtropical Climate Zones - Yang, Sihang; Zhang, Yuguang; Cong, Jing; Wang, Mengmeng; Zhao, Mengxin; Lu, Hui; Xie, Changyi; Yang, Caiyun; Yuan, Tong; Li, Diqiang; Zhou, Jizhong; Gu, Baohua; et al. (Frontiers in Microbiology, 2017)
Introduction The ecological effects of global warming have widely been documented, with range shifts towards the poles at the rate of averagely 6.1 km per decade, and mean advancement of spring events by 2.3 days per decade (Camille and Gary, 2003). Forests are important ecosystems that support a large proportion of global biodiversity and store 45% of terrestrial carbon (Pan et al., 2011). In recent decades, substantial loss of carbon in forest soil has been observed, owing to positive feedbacks of forests to global warming via increasing fluxes of greenhouse gases (Bonan, 2008;Heimann and Reichstein, 2008). Broadleaved forests are major forest types in both temperate and subtropical climate zones (Wang et al., 2007). It is believed that (sub-)tropical forests are carbon neutral or carbon sinks, while temperate forests are usually carbon sources but can be turned into carbon sinks by reforestation and fire suppression (Pregitzer and Euskirchen, 2004). Subtle disturbance to the balance between respiration and photosynthesis can cause large changes in carbon pools from forests to atmosphere (Bonan 2008), hence it is important to elucidate mechanisms of soil biogeochemical cycling and predict ecological consequences of forest extension northwards by climate warming in the Northern hemisphere. Soil microbial community is the major component of terrestrial biodiversity and primary driver of biogeochemical processes such as biomass decomposition and greenhouse gas emission (Crowther et al., 2014). Therefore, understanding the mechanisms in shaping community taxonomic and functional gene structure is essential for predicting soil functional capacity and ecosystem functions. However, it has been hampered by high complexity of microbial communities. This challenge has been alleviated by the rapid development of high-throughput, next-generation sequencing technologies. Sequencing of 16S rRNA gene amplicon is powerful in fine-tuning assessment of microbial taxonomic composition. Meanwhile, development of a functional gene microarray (GeoChip) using information from public sequence database has enabled quantitative, accurate and rapid detection of hundreds of thousands of functional genes (Tu et al., 2014). GeoChip 5.0 contains more than 50,000 oligonucleotide (50-mer) probes that can detect 393 functional genes from carbon, nitrogen, sulfur and phosphorus cycling, metal reduction and resistance, and organic contaminant degradation (He et